Entrepreneurship in the Fashion Industry: The Case of Carolina Herrera - Saiz-Alvarez, J (IGI Global, 2021)
The fashion industry employs more than 300 million workers in the world with a turnover of more than a trillion dollars, which is equivalent to being the seventh economic power on the planet. The presence of Latin America and the Caribbean in this industry is growing, where Carolina Herrera is of fundamental importance. The objective of this chapter is to analyze the critical success factors of this company to recognize it internationally as an icon-brand and to study the entrepreneurial spirit of the company to be an example for new generations (and even to competitors). A SWOT analysis will be made complemented by a PESTEL analysis to achieve these goals. The chapter ends with conclusions and perspectives after COVID-19. © 2021, IGI Global. All rights reserved.